Aerodynamic stability of long span suspension bridges with low torsional natural frequencies. (1st August 2016) - Andersen, Michael Styrk; Johansson, Jens; Brandt, Anders; Hansen, Svend Ole
Highlights: 18 bridge section models were tested in a wind tunnel. Tests were conducted at different torsional-to-vertical frequency ratios​. Flutter was avoided when the torsional frequency was lower than the vertical. Divergence followed by stall caused oscillations if the torsional stiffness was low. Design criteria for a non-flutter design principle are suggested. Abstract: Classical flutter of suspended bridge decks can be avoided if the torsional frequencies are lower than the vertical. Wind tunnel tests of single boxes and twin box section models with torsional natural frequencies above and below the vertical frequency has been conducted. Flutter was avoided in all tests where the torsional frequency was lower than the vertical. But too low torsional stiffness caused large static displacements of the girder at medium–high wind speeds and steady state oscillations driven by a combination of torsional divergence and stalling behavior at the critical wind seed. In order to design aerodynamically stable suspension bridges with low torsional natural frequencies it is suggested to increase the mass moment of inertia and provide adequate torsional stiffness by the main cables spacing.